Light-cured chitosan-based hydrogels for bone healing An integrative review - Costa, Amélie Charlotte Anne da (2023)
Introduction: Bone healing is a process that can be improved by using techniques such as bone graft or bone tissue engineering. Light-cured chitosan-based hydrogels are a very promising bone tissue engineering approach to help with bone healing. Purpose: The main aim of this study was to perform an integrative review on the effects of chitosan-based hydrogels on enhanced bone healing. Material and Methods: A search was performed on the PubMed database, using the following key terms: “chitosan” AND “riboflavin” OR “photoinitiator” OR “methacrylate” OR “methacrylamide” OR “photo” AND “bone OR “osteoblast”. Articles in English language, published from January 2009 to May 2023 were included. Results: A total of 23 studies were included in the present review. The selected studies assessed hybrid chitosan-based hydrogels with the incorporation of different bioactive compounds. Discussion: Bioactive components such as collagen, hyaluronic acid, peptides, growth factors, and recombinant proteins significantly improved the cell viability of osteogenic cells at around 80 and 90%. The addition of inorganic fillers and the intricate cross-linking of the organic matrix increased the mechanical strength and pores’ network of the hydrogels leading to a balanced degradation. Additionally, the incorporation of antimicrobial compounds such as vancomycin induce the inhibition of bacteria growth surrounding the hydrogels. Conclusions: Several hybrid chitosan-based hydrogels can be developed by adding bioactive inorganic fillers and biomolecules. The combination of bioactive compounds and molecules provide multi-function effects regarding the stimuli of osteogenic cells and inhibition of bacteria that is beneficial for the bone healing process.